2020
DOI: 10.1016/j.jstrokecerebrovasdis.2020.105419
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Brain Death Determination and Apnea Testing for Patients with COVID-19

Abstract: Introduction Apnea testing remains essential for the clinical evaluation of brain death determination. In patients who test positive for SARS-CoV-2, disconnecting the patient from the ventilator and introducing high flow oxygen into the endotracheal tube increases the risk for aerosolization of airway secretions and exposure of the examiner. Methods Case report of a patient with an intracerebral hemorrhage that evolved to significant cerebral edema and herniation, who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…During the prospective study period, there were 182 brain death evaluations, of which 138 involved apnea testing and 130 patients were declared dead after AT. The study period coincided with the recent coronavirus pandemic, during which apnea testing was, for a time, modi ed or in some cases, avoided out of concern for aerosolizing infectious particles [14][15][16]. Those apnea tests were excluded and did not have recruitment maneuvers performed.…”
Section: Resultsmentioning
confidence: 99%
“…During the prospective study period, there were 182 brain death evaluations, of which 138 involved apnea testing and 130 patients were declared dead after AT. The study period coincided with the recent coronavirus pandemic, during which apnea testing was, for a time, modi ed or in some cases, avoided out of concern for aerosolizing infectious particles [14][15][16]. Those apnea tests were excluded and did not have recruitment maneuvers performed.…”
Section: Resultsmentioning
confidence: 99%
“…There have also been new additions to the literature on apnea testing since publication of the WBDP. [114][115][116][117][118] A 2021 publication of a scoping review of publications on apnea testing from 1980 to 2019 provided additional knowledge about variability in apnea testing prior to publication of the WBDP. 114 The authors reported a variety of modifications, monitoring techniques, and complication rates and emphasized the need for updates to apnea testing protocols with the intent to strive for uniformity.…”
Section: New Publications Related To Apnea Testingmentioning
confidence: 99%
“…118 Finally, a few publications addressed the challenges of apnea testing in patients with COVID-19, which was nonexistent when the WBDP was written. [115][116][117]119,120 Beyond Minimum Clinical BD/DNC Determination…”
Section: New Publications Related To Apnea Testingmentioning
confidence: 99%
“…Although there is no international consensus on the apnea test procedure, the most frequently chosen method is the "traditional apneic oxygenation" technique which requires the patient to be disconnected from the ventilator before observing spontaneous breathing. However, there is a high risk of aerosol formation in this method, in which the oxygen insufflation technique is used, and the risk can be reduced by clamping the endotracheal tube in this technique 5 . Aerosol generation and the risk of viral transmission during apnea test can also be reduced but not eliminated when continuous positive airway pressure delivered through a ventilator is used as a means of apneic oxygenation 6 During the pandemic process RT-PCR tests were required for every potential donor with a Glasgow Coma Scale score of 6 or lower, in line with the recommendations of the Scientific Advisory Board in our country, and it had been suggested to investigate travel and contact history and COVID-19 symptoms 11 .…”
Section: Introductionmentioning
confidence: 99%